Investigation of the p-[sigma]0 interaction via femtoscopy in pp collisions - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; Ohlson, Alice; et al. (Physics letters, 2020)
This letter presents the first direct investigation of the p-Sigma(0) interaction, using the femtoscopy technique in high-multiplicity pp collisions at root s = 13 TeV measured by the ALICE detector. The Sigma(0) is reconstructed via the decay channel to Lambda gamma, and the subsequent decay of Lambda to p pi(-). The photon is detected via the conversion in material to e(+)e(-) pairs exploiting the capability of the ALICE detector to measure electrons at low transverse momenta. The measured p-Sigma(0) correlation indicates a shallow strong interaction. The comparison of the data to several theoretical predictions obtained employing the Correlation Analysis Tool using the Schrodinger Equation (CATS) and the Lednicky-Lyuboshits approach shows that the current experimental precision does not yet allow to discriminate between different models, as it is the case for the available scattering and hypernuclei data. Nevertheless, the p-Sigma(0) correlation function is found to be sensitive to the strong interaction, and driven by the interplay of the different spin and isospin channels. This pioneering study demonstrates the feasibility of a femtoscopic measurement in the p-Sigma(0) channel and with the expected larger data samples in LHC Run 3 and Run 4, the p-Sigma(0) interaction will be constrained with high precision.
Gesehen am 03.05.2021
Im Titel ist "Sigma" als griechischer Buchstabe dargestellt, die Zahl 0 ist hochgestellt
The ALICE collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D. Weiser, B. Windelband, A. Yüncü [und 981 weitere]